Pandemic behind bars: COVID-19 impact on mental health and suicide prevention. - JUNKER, GARY; SCHULT, DEBORAH; AUFDERHEIDE, DEAN (Corrections Today)
The article examines the impact of COVID-19 pandemic on mental health and suicide prevention in prisons. It discusses the impact of COVID-19 on suicide risk among prisoners and risk factors including lack of relationships, conditions of confinement known as restrictive housing or segregation, reduced engagement in programming and social isolation. Strategies to decrease suicide risk include mental health care access, positive psychology and resilience and responsive communication.